O TRATAMENTO ARQUIVÍSTICO EM DOCUMENTOS PESSOAIS E AS INSTITUIÇÕES CUSTODIANTES NO SUDESTE BRASILEIRO - Lima Santos, Melânia (Prometheus - Journal of Philosophy., 2020)
Throughout their existence, people, in general, produce their records, their stories and their experiences. It is through the documents that we know their customs, their interests and their life in society. Documents become important testimonies of moments that are often immortalized in the different types of materials, objects and papers that we have accumulated yhroughout our existence. Therefore, it is known that the documents produced and kept by people reveal their trajectory, their habits, their language, their culture and their values, constituting one that is usually called: personal archives. Thus, this work intends to present a brief overview of the personal archives held in public and private entities, demonstrating, through the institutional function and mission, how the safeguarding of documentary items is maintained and made available to the public. For the study, an institution was chosen from each city in the Southeast region, which keeps part of the files of four Brazilian personalities, being analyzed in a comparative perspective. As a method, a quantitive-qualitative, exploratory and bibliographic approach is used. The data collection instrument is carried out through the case study. As a method, the comparative was used. The analysis is made from the information collected on the researched sites, based on the theories discussed in the surveyed framework. The results, on the other hand, revealed that custodian institutions in Brazil fulfill their role, namely: custody, preservation and access to the documents that are under their protection in their domain.